2021
DOI: 10.1002/jts.22688
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Clinician‐Reported Self‐Efficacy in Treating Trauma‐Exposed Youth

Abstract: Clinicians' self-efficacy with regard to delivering evidence-based interventions (EBIs) to youth is an important target for both improving EBI use in the community and mitigating the risk of clinician burnout and turnover. Examining predictors of clinician self-efficacy to treat trauma-exposed youth is, therefore, an important step for informing the design of implementation strategies to enhance the mental health workforce's capacity to deliver EBIs in this population. We examined predictors of clinician self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Higher self-beliefs can reciprocally lead to positive attitudes and openness towards learning and mastering new practices. Adequate training and supervision in structured, multifaceted EBPs like TF-CBT can then enhance clinicians’ skills and perceived competency and positive attitudes [ 43 , 54 ]. This increase in perceived self-efficacy will be reinforced when using TF-CBT becomes accompanied with actual improvements in traumatized children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher self-beliefs can reciprocally lead to positive attitudes and openness towards learning and mastering new practices. Adequate training and supervision in structured, multifaceted EBPs like TF-CBT can then enhance clinicians’ skills and perceived competency and positive attitudes [ 43 , 54 ]. This increase in perceived self-efficacy will be reinforced when using TF-CBT becomes accompanied with actual improvements in traumatized children.…”
Section: Discussionmentioning
confidence: 99%
“…According to the job demandsresources theory [48], job and personal resources like access to trauma-specific trainings and the sense of mastery and self-efficacy can either buffer the negative effects of job demands and reduce job strain [33] or facilitate achieving occupational goals by increasing work engagement [49]. Empirical studies, also from Norwegian CAMHS [83] have shown that TF-CBT is indeed highly effective, and a positive association of higher self-efficacy with both training in TF-CBT [54] and higher levels of compassion satisfaction [82] have been recently reported. Although perceived self-efficacy is not measured in the present study, the ProQOL-V items by which compassion satisfaction is measured in the present study include statements that can reflect therapists' perceived level of self-efficacy (e.g., "I am pleased with how I am able to keep up with professional updates").…”
Section: Between Group Differencesmentioning
confidence: 99%
See 1 more Smart Citation